Unreported Crime. Polish Findings of ICVS '86 and '92 Compared (Archives of Criminology, 1998)
Poland participated in all the three ICVS series conducted so far, and research was each time carried out by the Law Enforcement Institute. However, due to Poland’s underdeveloped telephone network, only the 1989 (Warsaw) survey used the method of telephone interview. The next two series, of l992 and 1996, examined relative big and carefully selected national samples of households (of assumed over 2 thousand respondents in 1992 and over 4 thousand in 1996), but the traditional face-to-face method was used. The field survey was carried out by renowned opinion survey centers supervised by the Institute. Particularly worth stressing is the fact that Poland was probably the only country involved in ICVS where surveys started exactly on time. It should also be added that we achieved more than satisfactory completion rates: the proportion of refusals was about 5% in 1992 and 14% in 1996, and thus much smaller compared to survey using the CATI (Computer Assisted Telephone Interview) method. This of course influenced the quality of our findings.In 1995, Polish people most often fell victim to consumer offenses (14.2%) and carbreaking (10.1%). Rather high were also the proportions of interntional car damage (9.6%) and theft of personal property (5.6%). In the remaining cases, victimization coefficients never went beyond 5%.Compared to 1991, victimization structure underwent no greater changes. Of the 13 types of offenses examined, only 5 showed increases or decreases by more than 1% in the proportion of victims; the biggest change was 2.6% which was in practice still within the bounds of measurement error. Generally it seems, therefore, that in l991 and l995 unreported crime became stabilized in Poland as opposed to reported crime which in most cases still shows rather a strong upwards trend.Thus while robbery rate was 1.7 in 1991, the 1995 rate was higher by a mere 0.1% and amounted to 1.8. It should be added, though, that also our findings confirm the thesis as to a growing brutality of robbery and a change in the perpetrators’ modus operandi. For example, the proportion of robberies committed by one person went down from 25.2 to 18.8%. Besides, a larger proportion of respondents said to robbers had been armed. Also the „effectiveness” of robbery went up: a greater proportion (43.6 compared to 37.7%) stated that the robbers had actually managed to steal something. On the other hand,  though, which is against expectations, also the proportion of statements as to robbers being armed went down. To our great surprise it appeared, too, that among the 13 countries participating in the survey (where ICVS '96 was carried out on the national sample) Poland had the highest robbery rate.The rate of batterics (attempts) went down from 4.2 in 1991 to 3.7 in 1995, that is by 0.5%. Yet characterization of those acts would be incomplete if we failed to mention that, in that same period, the proportion of batteries by assailants armed with dangerous weapons or firearms went up from 6 to 20.6%, and the weapons or firearms were actually used in 35.2% of cases. The more serious nature of batteries is also manifested by a considerable growth in the number of cases in which the victims needed a doctor: 32.8% in 1995 compared to 22.4% in 1991. As opposed to robbery, though, the battery rate in Poland is among the relatively low.Reduced most among acts with the element of aggression in years under comparison was the number of sex ofenses: from 3.6% in 1991 to 1.5% in 1995, that is by 2,1% (the difference being significant). It should be mentioned, though, that while none of the victims of this kind of act actually called it rape in 1992, the proportion of such persons was as much as 7% in the most recent survey. There was at the same time a rather considerable drop (by over 7%) in the number of victims who called the act ,,indecent assault”. Thus also the structure of this kind of acts underwent a specific change. What can be treated as indirect indication of seriousness of sex offenses are also statements as to criminal nature of the act (,,Do you consider the act an offense?”). Also those statements („Yes” answers) confirm the drop in the number of more serious acts of this kind (from 6.1% in 1992 to 53.5% four years later). Also reduced (by over 10%) was the proportion of statements as to serious or very serious nature of the incident. The relatively small danger of sex offenses in Poland is confirmed by confrontation with international data: in three countries only, the proportion of victims of such acts is smaller than in Poland.The growth of car sales situates Poland among European leaders. It was therefore interesting to find out about the impact of the growing number of cars on offenses ,,against cars”. According to the criminal opportunity theory, a considerable growth in the numer of such offenses could be expected, caused by increased ,,supply”. It appeared, however, that the growing number of cars failed to bring about any significant growth in the number of offenses against cars. Proportions of victims of car theft and intentional car damage (among car owners) went up in the period under analysis by a mere 0.1% (from 1.4% to 1.5% and from 9.5% to 9.6% respectively); in the case of victims of carbreaking, the proportion went down by 0.4% (from 10.5% to 10.1%). From comparison with international data on offenses ,,against cars'' it follows that Poland is among countries with medium-level threat of car theft; instead, the threat of car-breaking and international damage to cars is above the average, Poland ranking second and fourth respectively.Greater changes were found in the cases of one-track vehicles: motor-cycles and bicycles. In both cases, the numer of victims went down: by 1.8% in the case of motorcycle thefts, and by 1.1% in the case of bicycle thefts; it is worth stressing that the drop was significant. In most countries under research, thefts of one-track vehicles, bicycles in particilar, are a much greater problem than in Poland.Among the analyzed acts against property, the greatest drop (by 2.5% which makes the difference significant) was found in the case of the number of victims of theft of personal property. A sub-category of this group was pocket-picking inquired about by a filtering question. Worth stressing here is a drop in proportion of pocket-picking among thefts of personal property: from 83.2% in 1991 to 71.3% four years later, that is by over 10%. However, Poland is stil among countries with the greatest threat of thefts of personal property, pocket-picking included (which is rather understandable the fact considered that most Polish people still carry cash instead of a credit card).There was also a slight downward trend in the proportion of victims of housebreaking, both attempted (by 0.5%) and committed (by 0.1%). The proportions of victims of housebreaking (attempted and committed) situate Poland among countries with a medium-level threat of that type of offense.Compared to the previous survey. There was a considerable growth (by 2.6% which makes the difference significant) in the number of victims of consumer frauds. Instead, the number of victims of corruption of State officials went down by 0.7%. As follows from comparisons with international data, Poland is among the countries with the highest threat of such acts. Particularly alarming is the fact of as high a level of corruption in both post-communist countries included in the sample: in Poland and Czech Republic alike, that level is several times higher compared to the remaining countries.Similar trends can generally be found in a comparison of numbers of offenses per l00 respondents; here, however, differences in dynamics of individual offenses can be noticed with greater clarity. Striking is also a growth in the rate of batteries (attempts): from 6.7 in 1991 to 7.4 in 1995.The general victimization risk index is now 23 in Poland; it was 27 in the previous survey which means a drop by 4 points. From a comparison of that index with its foreign counterparts it follows clearly that the general extent of crime is not too big in Poland. At any rate, Poland is below the average of 11 Western countries of which 3 only (Finland, Austria and North Ireland) have indices lower than the Polish one.Yet underlying this apparent stabilization of unreported crime in the discussed period is a rather considerable growth or drop in the numer of repeated victims.Thus the proportion of repeated victims (respondents who fell victim to a given type of offense on at least two occasions during the last 12 months) went up in the case of car thefts by 9.1; in the case of car-breaking – by as much as 15.1; in the case of international damage to car – by 4.7; in the case of theft of personal property – by 8.2; in the case of burglary - by 4.9; in the case of robbery - by 9.7; and in the case of battery (attempt) – by  8.1. The only proportions that showed a downward trend were those of victims of motorcycle theft (by l0.2); bicycle theft (by 1.1); and sex offences (by 13.2). This is therefore a significant growth in concentration of crime (a greater numbers of acts against those same persons). Interestingly, the direction of the trend is not always the same in the case of one-time and repeated victims. For example, the proportion of victims of car-breaking went down by 0.4 in the period analysis while that of repeated victims went up by over 15.Differences in the dark number between individual offenses are very big. As follows from the findings of the Polish part of ICVS ’96, they range from nearly 100% (in the case of consumer frauds),to under 10% (in the case of car thefts). Besides, against expectations, the dark number was by no means the highest in the case of sex offences (it was very high, though: 88%).Generally it can be stated that the lowest dark number is found in the case of willful taking of property of considerable value, that is car and motor-cycle thefts, burglaries and bicycle thefts (7.2%, 21%, 45.7% and, 55.2% respectively). Seldom reported, instead, are thefts of personal property: the dark number is here nearly 80%. Also robbery and battery have a high dark number of 62.5% and 68.8% respectively. The dark number is definitely the highest (nearly 100%) in the case of the above-mentioned consumer frauds and corruption.As regards the inclination to report an offense, differences between the findings of the 1992 and 1996 survevs were greater but by no means explicit. Generally, there was an increase in the numer of reported aggressive offenses: batteries (by 6.4%); robberies (by 6.1%); and sex offenses (3.6%). The opposite trend was found in the case of reported thefts. The greatest was the drop in reported motor-cycle thefts (by 10.1%) and carbreaking (by 8.6%; here, the difference was significant). The proportion of reported bicycle thefts went down by 2.2%; that of cars – by 0.2%; and that of thefts of personal property remained unchanged. There was, instead, a rather considerable growth in the proportion of reported damages to car (by 3.2%) and burglaries (by 6.1%).The dark number of offenses is still very high in Poland, much higher than in the West. There, the average proportion of reported offences in the groups of six acts under analysis amounts to 50; in Poland, it is merely 34. This means that police data on crime in Poland are not too reliable as they say very little about its actual extent.Compared to the previous survey, the people's feeting of safety increased rather considerably which may also indirectly confirm the thesis that generally, there is no actual growth in crime in Poland. There was a growth by 11 points in the proportion of respondents who said they felt safe strolling in their neighborhood after dark; the proportion of those who said they avoided specific streets for reasons of safety dropped by one-third; and the proportion of persons who considered it highly probable that they would fall victim to burglary during the next 12 months was reduced by half.Despite the rather explicit growth in the Poles' feeling of safety, there was also a most considerable growth in their critical opinions on police work. Thus the proportion of respondents who consider police actions to control crime ineffective went up by a half. Respondents also spoke of fewer policemen patrolling the streets: the proportion of those who said that a police patrol turned up in their neighborhood at least once a day went down from 27.5 top 23.3. Mentioned more often among reasons for not reporting an offense was idleness of the police. Persons dissatisfied with the treatment they received from the police prevailed among those of the victims who had reported the last offense against them. The proportion of the satisfied was the highest among victims of reported battery: 40%. Among victims of reported robbery, instead, the proportion of those satisfied with the treatment they received from the police was somewhat under 30%. Worth mentioning in this context is also a considerable drop in effectiveness of police work as regards regaining of stolen cars. While the 1992 findings indicated a satisfactory effectiveness in this respect (in 77.4% of cases, the owners got their stolen car back) there were a mere 45.l% of such cases in the 1996 survey.Crowning this definitely unfavorable appraisal of police work is the nearly three times' growth in the number of persons who mentioned police officers among officials demanding a bribe (31.9% compared to previous 11.4%). It appears, therefore, that stable crime and growing feeling of safety is not accompanied - as one might expect – by more favorable appraisals of police work. This results probably from the fact that the people's expectations in this respect went even higher up since 1992.